A Novel Optimal PI Parameter Tuning Strategy to Improve Constant Switching Performance of Direct Torque Control - Sundram Ramahlingam; Auzani Jidin; Tole Sutikno (Institute of Advanced Engineering and Science, 2016)
This paper presents a novel method of optimal Propotional-Intergral (PI) controller’s parameter tuning strategy in-order to improve the Constant Switching Performance of 3-phase DTC shceme. The Direct Torque Control (DTC) sheme is acknowledged to provide fast decoupled control over the torque output and stator flux via a simple control structure. However, DTC sheme has two major downsides, which are the inconsistent inverter switching frequency and high torque output ripple. The main reason that contributes to these tribulations is the usage of hysteresis comparators in order to control the output torque. The realization of PI based controller method as replacement of hyterisis controller in DTC system able to provide significant solutions to over come the fall back while retaining the simple control structure of conventional DTC. The combination usage of higher sampling controller DS1004 and also 3-level CHMI in this system can further minimize the output torque ripple by providing higher resolution with lower digital error and greater number of vectors. This paper presents detail explanation and calculation of optimal PI parameter tuning strategy consecutively to enhance the performance of 3-level DTC system. In order to verify the feasibility of the proposed method experimentation, the proposed method is compared with convention DTC system via simulation and experiment results.